2020
DOI: 10.1177/1542316620945968
|View full text |Cite
|
Sign up to set email alerts
|

Trust and Prospective Reconciliation: Evidence From a Protracted Armed Conflict

Abstract: Traditional approaches to international aid deal with post-conflict risks focusing on external safeguards for peacebuilding, leaving local social enhancers playing a subsidiary role. Trust has long been highlighted as a key factor that can positively affect sustainable peace efforts by reducing intergroup hostility. Surprisingly, most post-conflict studies deal with trust as a dependent variable. Using a cross-sectional multi-method field study in Colombia, we assess the impact of trust on prospective reconcil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Since Allport's work, other scholars have found similar results around the world (Casas‐Casas, Mendez and Pino 2020; Noor et al. 2015; Orejuela and Restrepo‐Plaza 2021).…”
Section: Argument: Fear Familiarity and The Reintegration Of Former C...mentioning
confidence: 62%
See 1 more Smart Citation
“…Since Allport's work, other scholars have found similar results around the world (Casas‐Casas, Mendez and Pino 2020; Noor et al. 2015; Orejuela and Restrepo‐Plaza 2021).…”
Section: Argument: Fear Familiarity and The Reintegration Of Former C...mentioning
confidence: 62%
“…While fear may be one of the dominant, emotional drivers of human behavior, ultimately people are social beings who depend and thrive on their work and interactions with others. There is a substantial body of research regarding the role played by contact, interactions, and familiarity in reducing fear of the other as well as the more ambitious goal of reconciliation (Casas-Casas, Mendez, and Pino 2020;Nooret al 2015;Orejuela and Restrepo-Plaza 2021;Swart et al 2011). The roots of much of the research regarding the role played by experience with the other in reducing fear is found in Gordon Allport's "contact hypothesis" (1954).…”
Section: Familiarity Engagement and Trustmentioning
confidence: 99%
“…A recent field study conducted in Colombia (Casas et al., 2020) indicated that correcting Colombians' erroneous meta‐perceptions of the FARC (The Revolutionary Armed Forces of Colombia—People's Army), reduced anti‐FARC beliefs and attitudes, and increased support for pro‐FARC policies and for the peace process (these effects persisted for at least 3 months following the original intervention). In another recent finding, Lees and Cikara (2020) conducted seven experimental studies, which indicated that informing participants of the inaccuracy of their beliefs reduced negative out‐group attributions and was more effective for those whose group meta‐perceptions were more inaccurate.…”
Section: Can Corrective Information Deescalate Erupted Inter‐group Vi...mentioning
confidence: 99%
“…Considering the peace studies literature and an analytical framework such as the one proposed by Casas and Méndez (2017b) and Casas-Casas et al (2020), Prolongar Foundation has created a reconciliation model through a systemic approach that addresses directly two of these three dimensions: the intrapersonal and interpersonal dimensions of human and social interactions. The third dimension should be addressed when institutional and programme design incorporates art-based initiatives into standard rules, plans and policies.…”
Section: Literature Review: Creative Art-based Reconciliation Models ...mentioning
confidence: 99%
“…In this dimension, peace agreements create political and social space where a whole new range of negotiations occurs (Lederach, 2005). In these contexts, the redefinition of institutions should also include the transformation of relational spaces through the use of metaphors where people ‘can actively engage in initiatives for constructive change’ (Lederach, 2005, p. 47). Considering the peace studies literature and an analytical framework such as the one proposed by Casas and Méndez (2017b) and Casas‐Casas et al (2020), Prolongar Foundation has created a reconciliation model through a systemic approach that addresses directly two of these three dimensions: the intrapersonal and interpersonal dimensions of human and social interactions. The third dimension should be addressed when institutional and programme design incorporates art‐based initiatives into standard rules, plans and policies.…”
Section: Literature Review: Creative Art‐based Reconciliation Models ...mentioning
confidence: 99%